Upaya Meningkatkan Pemecahan Masalah Matematis Siswa melalui Penerapan Model Problem Based Learning - Sartika Juwita Br Sinaga; Dwi Novita Sari; Desniarti Desniarti; Burlianda Burlianda (Departement of Mathematics Education, 2024)
This Classroom Action Research aims to determine the improvement of students' mathematical problem-solving skills through the application of the Problem-Based Learning model. The subjects in this class action research are all students of class XI Merdeka Jaya SMA Negeri 1 Tanjung Morawa even the semester of the 2023/2024 academic year consisting of 35 students (13 male students and 22 female students). This research data is in the form of quantitative data obtained from mathematical problem-solving ability tests with statistics material and qualitative data in the form of student activity data. The data analysis technique used in this research is simple statistical analysis. The results of data analysis showed that there was an increase in students' mathematical problem-solving ability through the application of the Problem-Based Learning model. The results showed an increase in students' mathematical problem-solving ability in each cycle where cycle I amounted to 57.14%, and cycle II amounted to 88.57%. Then the results showed that student activity in the learning process in each cycle where cycle I amounted to 70.83%, and cycle II amounted to 91.67%. So it can be concluded that this class action research, namely through the application of Problem-Based Learning, can improve students' mathematical problem-solving skills on matrix material in class XI Merdeka Jaya SMA Negeri 1 Tanjung Morawa.